VANDA STONIENE – ACADEMICIAN AND SCIENTIST OF VILNIUS UNIVERSITY - TARASKEVIČIŪTĖ, EGLĖ (Knygotyra, 2012)
Professor Vanda Stonienė was a well-known scientist of Vilnius University in the field of book science. Born in 1932, she died just before her 76th birthday, leaving many important scientific works written and things done. It is crucial to commemorate her and make a summing-up of her whole life’s successful career.The professor was best known for her analytical works published while working in the university. She also wrote a lot of popular science works, took part in editoring scientific publications. Professor V. Stonienė was a devoted academician. Her colleagues and students respected her for the commitment to work and book. She participated in many international conferences and worked for the public good. As an individual person, the professor collected her own library which was dedicated to the science of book.